CMD 2020 Opinion - Andrea Cavallini; Somyot Kaitwanidvilai (My University, 2020)
On behalf of Faculty of Engineering, we are honored and delighted to welcome all delegates and all the distinguished guests to the 8 th International Conference on Condition Monitoring and Diagnosis (CMD 2020) in the wonderful, bustling city of Bangkok, Thailand.We truly hope that this event will provide a unique platform for all participants to exchange ideas, discover novel opportunities, reacquaint with colleagues, meet new friends and broaden their knowledge.
Keywords: Machine Fault Diagnosis Techniques